(untitled) (International Seven Journal of Multidisciplinary, 2024)
Objective: To address some of the main pathologies that can bring the complaint of “itching” to the doctor’s office: Vulvar Psoriasis, Lichen Sclerosus and Vulvar Lichen Planus. This recurring complaint in doctors’ offices is characterized by itching or discomfort in the vulvar area, with a variety of causes. Methods: The research was carried out using a literature review based on data published on the CAPES Portal, SciELO and PubMed. Results: In the literature review it was possible to clarify that Vulvar Psoriasis, one of the differential diagnoses, is a chronic non-contagious dermatosis with intense itching, discomfort and scaling. Lichen Sclerosus, on the other hand, is a chronic dermal pathology of an intense inflammatory nature, with itching, pain and irritation of the mucosa, while Vulvar Lichen Planus is a chronic inflammatory disorder, with itching, pain, burning, dyspareunia and atrophy of the cultivar and vaginal architecture. Conclusion: This study concludes that failure to treat this complaint, which is common to all three conditions, has consequences that impact on the patient’s quality of life.